Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5367/te.2011.0087
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Factors Influencing Malaysian Tourism Revenue, 2002–2008

Abstract: The Malaysian tourism industry has flourished considerably over the years due to the growth of new tourist landmarks, together with its rich cultural heritage. The industry generated 6.78% of the total income from exports in 2008. This paper focuses on the dynamic relationship between macroeconomic factors and tourism revenue in Malaysia from January 2002 to December 2008. In this context, the authors investigate the presence of seasonal fluctuations in tourism revenue and examine the macroeconomic factors inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It is consistently used in modeling tourism demand and has been found to have explanatory power in the determination of tourism flows for both outbound and inbound countries [32]. The exchange rate has empirically been found to be an explanatory variable determining rises and falls in the number of inbound tourist arrivals [7] but in another study, changes in real exchange rates were shown to have mixed effects on tourism demand [33].…”
Section: Variables In the Literaturementioning
confidence: 99%
“…It is consistently used in modeling tourism demand and has been found to have explanatory power in the determination of tourism flows for both outbound and inbound countries [32]. The exchange rate has empirically been found to be an explanatory variable determining rises and falls in the number of inbound tourist arrivals [7] but in another study, changes in real exchange rates were shown to have mixed effects on tourism demand [33].…”
Section: Variables In the Literaturementioning
confidence: 99%
“…Scholars emphasize tourism as a catalyst for economic growth, generating employment opportunities and elevating income levels (Brida et al 2018). National case studies provide insights into the substantial growth of Malaysia's tourism sector, contributing significantly to export income via the emergence of new destinations (Jayaraman et al 2011). Conversely, Borrego-Domínguez et al (2022 noted a positive link between GDP and the number of beds in tourism, with less impact on stock indices.…”
Section: Analyzing the Impact Of Tourism On Financial Marketsmentioning
confidence: 99%
“…According to Tourism Malaysia, 2015, the top five countries who visit Malaysia were Singapore, Indonesia, China, Thailand and Brunei which conquer the 75%. While the balance 25% tourist is from European, Middle East and Australian (Jayaraman et al, 2011).…”
Section: Problem Statementmentioning
confidence: 99%
“…The travel and tourism industry is progressing continuously in Malaysia, which is parallel with the worldwide tourism industry (Ying et al, 2015). The Malaysian tourism industry has succeeded significantly over the years due to the growth of new tourist landmarks, together with its rich cultural heritage (Jayaraman, Lin, Haron, & Ong, 2011). Over the past 10 years, Malaysia has experienced a significant increase in tourist arrivals (Habibi, 2017) which is one of the significant factors influencing on the country economy growth.…”
Section: Introductionmentioning
confidence: 99%